Synergistic effect of arsenic removal from petroleum condensate via liquid-liquid extraction: Thermodynamics, kinetics, DFT and McCabe-Thiele method - Kittamuk Purktimatanont; Vanee Mohdee; Ura Pancharoen; Kreangkrai Maneeintr; Wikorn Punyain; Anchaleeporn Waritswat Lothongkum (Heliyon, 2023)
As). The process of arsenic removal proved to be zero-order endothermic, irreversible and spontaneous reaction. The results obtained from the density functional theory (DFT) confirm that arsenic ions react with the synergistic extractant: effectively forming a covalent bond (As-S).
Keywords: Extraction and Separation Processes; Chemical and Physical Properties in Aqueous Solutions; Crystallization and Solubility Studies